An examination into the ethical acceptability of genetically modified foods in Kenya principled on Aristotelian Ethics - (:unkn) unknown (My University, 2015)
Ethics is a branch of Philosophy which studies free human acts from the point of view of their moral value (goodness or badness) in relation with the last end of man( Debeljuh,2006). Ethics is able to ascertain what man‘s final goal is and to determine the type of behaviour that will lead him to that final goal which ultimately should give him happiness. In th is paper I would like to examine the ethical acceptability of GM foods in Kenya using the Aristotelian understanding of e thics. For Aristotle , e thics is based on achieving the chief good for man which he called eudaimonia ( ̳happiness‘). He said that eudaim onia is something that is ―final and self sufficient and is the end that our human action tends toward. Aristotle discovered that this happiness if found by man exercising his rational nature which gives him the capacity to direct himself to the good in ev ery action. Looking at the GM foods from this point of view, the paper will try to examine if GM foods enhance the nature of man by taking into consideration his rational nature as well as promoting the common good of man. Anything that goes against his na ture would be considered morally unacceptable. Aristotle defines the common good as the perfect goal of the state which requires an admission of the indiv idual's basic right in society. This basic right means the right of everyone to the opportunity to fre ely shape his life by responsible action, in pursuit of virtue and in accordance with the natural moral law.
Conference paper
Ethics is a branch of Philosophy which studies free human acts from the point of view of their moral value (goodness or badness) in relation with the last end of man( Debeljuh,2006). Ethics is able to ascertain what man‘s final goal is and to determine the type of behaviour that will lead him to that final goal which ultimately should give him happiness. In this paper I would like to examine the ethical acceptability of GM foods in Kenya using the Aristotelian understanding of ethics. For Aristotle, ethics is based on achieving the chief good for man which he called eudaimonia (‗happiness‘). He said that eudaimonia is something that is ―final and self sufficient and is the end that our human action tends toward. Aristotle discovered that this happiness if found by man exercising his rational nature which gives him the capacity to direct himself to the good in every action. Looking at the GM foods from this point of view, the paper will try to examine if GM foods enhance the nature of man by taking into consideration his rational nature as well as promoting the common good of man. Anything that goes against his nature would be considered morally unacceptable. Aristotle defines the common good as the perfect goal of the state which requires an admission of the individual's basic right in society. This basic right means the right of everyone to the opportunity to freely shape his life by responsible action, in pursuit of virtue and in accordance with the natural moral law.
Keywords: Aristotelian Ethics; ethics; genetically modified foods; Kenya; object; intention; circumstances